MAKNA ETIS “PUNJUNG NASI SAWO” PADA ACARA PERNIKAHAN SUKU REJANG DI KECAMATAN BATIKNAU KABUPATEN BENGKULU UTARA - Irsal Irsal (Manthiq, 2017)
Abstract: This research was  motivated by the  reality on the  ground  that there  was  a traditional  ceremony in Rejang tribe “Punjung Nasi Sawo”. The Rsearcher assumed that this tradition had a religious or moral message. The formulation of the problem in this study was what the symbolic meaning contained from the “Punjung Nasi Sawo” at the wedding of Rejang tribe in Batiknau  district of North Bengkulu,  what the ethical was contained in the procession of Punjung  Nasi Sawo at the wedding of Rejang tribe in Batiknau  district of North Bengkulu and how the manufacturing process and materials used  in presenting the “Punjung  Nasi Sawo”. This research had the goal was  to determined and  analyzed  the symbolic  meaning contained from the “Punjung  Nasi Sawo” at the wedding of Rejang tribe in Batiknau  district of North Bengkulu, to analyze the meaning of ethical contained in procession of “Punjung Nasi Sawo” at the wedding of Rejang tribe in Batiknau district of North Bengkulu and to determine and  analyze  the manufacturing process and  materials used  in the presentation of the “Punjung Nasi Sawo”?.  To obtained information on  the  ground,  the  researcher used  a  type  of field research with  a qualitative  approach. Based  on the results  of the study “Punjung  Nasi Sawo” on the Marriage Event of Rejang tribe in Batiknau district of North Bengkulu revealed that the activity was performed at the time of Raja Penghulu Consensus (madeak kutai),  the event  was attended by community leaders that consists  of traditional  leaders, religious  leaders, government of the  village and  the  general  public.  The activity of Raja Penghulu Consensus (madeak kutai)  included several  items  of rejang  tribe, one  of them  was  “Punjung  Nasi Sawo” and  the  event was held in the outdoors (taruf). Besides, these activities showed that the implementation of the Raja Penghulu Consensus (madeak kutai) which included one of rejang tribe “Punjung Nasi Sawo” that had some moral values, ethical,  social, anthropology and religion. In addition,  Punjung  Nasi Sawo symbolized as a noble  hope  against both  the bride  and  groom,  as a form of guarantee, as a form of application for license to community leaders, religious leaders and the surrounding communities and to establish with nurture event Silahturahim rope. This is in accordance with the customary slogan of Rejang tribe “ adat bersendikan syara’’, syara’ bersendikan kitab Allah. It means that the culture  remains preserved all relied on the law and the provisions of Islamic Sharia.